Supporting context-aware adaptive and personalized mobile learning delivery: Evaluation results from the use of UoLm Player - Gomez, S.; Zervas, P.; Sampson, Demetrios; Fabregat, R. (2013)
Over the last decade, several research initiatives investigate the potentials of the educational paradigm shift from the traditional one-size-fits-all teaching approaches to adaptive and personalized learning. On the other hand, mobile devices are recognized as an emerging technology with the potential to facilitate teaching and learning strategies that exploit individual learners' context. This has led to an increased interest on context-aware adaptive and personalized mobile learning systems that aim to provide learning experiences delivered via mobile devices and tailored to the educational needs, the personal characteristics and the particular circumstances of the individual learner or a group of interconnected learners. In previous work, a context-aware adaptive and personalized mobile learning system has been proposed, namely the UoLm Player. In this paper, we present initial evaluation results from its use, so as to analyze the effectiveness of the proposed tool towards delivering adaptive and context-aware learning activities. © 2013 IEEE.